Adversarial, ludic and ritual nature of discursive interactions in a trial - Boginskaya, Olga (Penerbit Universiti Kebangsaan Malaysia, 2022)
This article makes a contribution to the study of courtroom discourse assuming that interactions in a trial are of agonal nature. The study aims to identify and explore key aspects of agonal interactions (adversarial, ludic and ritual) and rhetorical agonal strategies employed in a trial. The study revealed the following adversary strategies used by the prosecutor and the defense attorney to win the struggle: discrediting, refutation and objection. The components of courtroom interactions such as participants struggling to win, referees overseeing the game and selecting the winner and spectators observing the performance indicate its ludic nature. Rituals as an integral component of both games and competitions ensure fair proceedings, regulate participants’ behavior, and organize agonal interactions, being the backbone of courtroom trials. The adversary, ludic and ritual components of agonality determine the nature of courtroom activities whose formal goal is to restore justice, and the actual one is to select the winner. The study concluded that these three components of agonality are interrelated: competition is a sign of game, and ludic elements are an integral characteristic of any competition as a product of culture; both competition and game are regulated by rituals and involve participants pursuing opposing goals.